2021
DOI: 10.3389/fonc.2021.608433
|View full text |Cite
|
Sign up to set email alerts
|

A Survival-Related Competitive Endogenous RNA Network of Prognostic lncRNAs, miRNAs, and mRNAs in Wilms Tumor

Abstract: Wilms tumor (WT) commonly occurs in infants and children. We evaluated clinical factors and the expression of multiple RNAs in WT samples in the TARGET database. Eight long non-coding RNAs (lncRNAs; AC079310.1, MYCNOS, LINC00271, AL445228.3, Z84485.1, AC091180.5, AP002518.2, and AC007879.3), two microRNAs (miRNAs; hsa-mir-152 andhsa-mir-181a), and nine messenger RNAs (mRNAs; TCTEX1D4, RNF133, VRK1, CCNE1, HEY1, C10orf71, SPRY1, SPAG11A, and MAGEB18) were screened from differentially expressed RNAs and used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The mutual influence of VRK1 and NOTCH pathways is related to the prognosis of laryngeal cancer ( de Miguel-Luken et al, 2016 ). VRK1 may provide new potential biomarkers for improving the prognosis and treatment of Wilms tumor (WT) patients by showing the WNT signaling pathway ( Liu et al, 2021 ). At the same time, the WNT pathway is also a crucial pathway for regulating epithelial mesenchymal EMT.…”
Section: Discussionmentioning
confidence: 99%
“…The mutual influence of VRK1 and NOTCH pathways is related to the prognosis of laryngeal cancer ( de Miguel-Luken et al, 2016 ). VRK1 may provide new potential biomarkers for improving the prognosis and treatment of Wilms tumor (WT) patients by showing the WNT signaling pathway ( Liu et al, 2021 ). At the same time, the WNT pathway is also a crucial pathway for regulating epithelial mesenchymal EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a risk score model, AC010894.3 was included in a four-lncRNA signature that accurately predicted the OS of OC patients, and its increased expression was associated with better survival [ 62 ]. Three other lncRNAs from our gene list, AC244502.1 , AP002807.1 , and AP002518.2 , were integrated into prognostic signatures for breast cancer, clear cell renal cell carcinoma, and Wilms tumor, respectively [ 65 , 66 , 67 ]. The lncRNA SNHG12 was selected as a candidate due to its inverse correlation between high expression levels and DNA hypomethylation in carboplatin-resistant OC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al found that the established ceRNA network was closely related in the progression and metastasis of ccRCC and 3 lncRNAs that may be related to ccRCC prognosis [ 21 ]. However, the difference or advantage of our study lies in a more accurate survival-related ceRNA network [ 22 , 23 ]. Among DERNAs, the total 2,307 DEmRNAs (761 downregulated and 1,546 upregulated), 54 DEmiRNAs (21 downregulated and 33 upregulated), and 1,456 DElncRNAs (459 downregulated and 997 upregulated) were screened.…”
Section: Discussionmentioning
confidence: 99%